2007
DOI: 10.1111/j.1471-4159.2007.04702.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel PIP2 binding of εPKC and its contribution to the neurite induction ability1

Abstract: Protein kinase C-e (ePKC) induces neurite outgrowth in neuroblastoma cells but molecular mechanism of the ePKCinduced neurite outgrowth is not fully understood. Therefore, we investigated the ability of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) binding of ePKC and its correlation with the neurite extension. We found that full length ePKC bound to PIP 2 in a 12-o-tetradecanoylphorbol-13-acetate dependent manner, while the regulatory domain of ePKC (eRD) bound to PIP 2 without any stimulation. To identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Shirai et al investigated the possibility of the direct binding of PKC ε to phosphatidylinositol 4,5-bis phosphate (PIP 2 ) and its correlation with the neurite outgrowth. They found that the direct binding of PKCε to PIP 2 can induce neurite and may influence the function of actin binding proteins [52]. They believed that the open conformation of PKC ε could interact with RhoGAP and/or PIP2, and this could be regulated by the binding of PKC ε to actin [8].…”
Section: Pkc ε and Neuritis Outgrowthmentioning
confidence: 99%
“…Shirai et al investigated the possibility of the direct binding of PKC ε to phosphatidylinositol 4,5-bis phosphate (PIP 2 ) and its correlation with the neurite outgrowth. They found that the direct binding of PKCε to PIP 2 can induce neurite and may influence the function of actin binding proteins [52]. They believed that the open conformation of PKC ε could interact with RhoGAP and/or PIP2, and this could be regulated by the binding of PKC ε to actin [8].…”
Section: Pkc ε and Neuritis Outgrowthmentioning
confidence: 99%
“…PKC activation by DAG can be mimicked by the addition of other compounds that bind the C1 domain, such as tumor promoting phorbol esters. PKCε may also be activated by other lipids, such as arachidonic acid, or phosphoinositide bisphosphate (PIP2) [15, 16]. …”
Section: Activation and Phosphorylation Of Pkcεmentioning
confidence: 99%
“…How PKCε regulates RhoA and Cdc42 is still unknown. We have recently shown that PKCε binds to phosphatidylinositol 4,5‐bis phosphate (PIP 2 ) and that the PIP 2 binding is necessary for PKCε‐induced neurite induction and its membrane localization [11]. The PIP 2 binding of PKCε may influence the function of actin binding proteins, leading to actin rearrangement and neurite induction.…”
Section: Neurite Outgrowthmentioning
confidence: 99%
“…Alternatively, PKCε may attenuate RhoA via RhoGAP, which is reported to bind to PKCε and induce neurite outgrowth [13]. Interestingly, the binding of full length PKCε to RhoGAP and PIP 2 is dependent on 12‐ O ‐tetradecanoylphorbol 13‐acetate, but εRD can bind to PIP 2 without 12‐ O ‐tetradecanoylphorbol‐13‐acetate [11,13]. These results suggest that the open conformation is important for the binding of PKCε to RhoGAP and PIP 2 .…”
Section: Neurite Outgrowthmentioning
confidence: 99%